Method for manufacturing all-solid-state battery
By heating specific parts of the outer film to soften the sealing resin layer and the insulating resin layer and absorb pollutants, the problem of electrode collector damage in the manufacturing of all-solid-state batteries is solved, and the battery performance and manufacturing quality are improved.
Patent Information
- Application Number
- CN202510218534.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-02-26
- Publication Date
- 2025-09-30
AI Technical Summary
During the manufacturing process of all-solid-state batteries, contaminants buried between the outer film and the electrode collector cause damage to the electrode collector, affecting battery performance and manufacturing quality.
Through the heating process, specific parts of the outer film are softened, especially the sealing resin layer and the insulating resin layer, to absorb existing pollutants and prevent them from burying the electrode collector. The outer film adopts a multi-layer structure to enhance durability and anti-short circuit performance.
It effectively prevents the damage of the electrode collector, improves the stability of the battery and the quality management of the manufacturing process, and enhances the durability and short-circuit resistance of the battery.
Smart Images

Figure CN120728012A_ABST
Abstract
Description
Technical Field
[0001] Cross-references between related applications
[0002] This application claims priority based on Japanese Patent Application No. 2024-058233, filed on March 29, 2024, the contents of which are incorporated herein by reference. Technical Field
[0003] The present invention relates to a method for manufacturing an all-solid-state battery. Background Art
[0004] Welding is used to join the tab to the electrode collector of the electrode stack included in an all-solid-state battery. Welding-based joining generates sputtering (metallic foreign matter), which sometimes remains as contamination on the surface of the electrode collector. Furthermore, when the tab is cut, shavings are generated, which sometimes remain as contamination on the surface of the tab. When the surface of the electrode collector is covered with an exterior film while contamination is present, the exterior film exerts a force that presses the contamination against the surface of the electrode collector. This can bury the contamination in the electrode collector and potentially damage it.
[0005] As a laminated battery for reducing the occurrence of defects during manufacturing caused by contamination between an outer film and an electrode current collector, for example, the following structure is known: it includes an electrode body and a laminated case for accommodating the electrode body, the laminated case having a multilayer structure including a sealing layer, a gas barrier layer, an outer layer, and an intermediate layer located between the sealing layer and the gas barrier layer, the gas barrier layer being an aluminum layer, and the intermediate layer containing 5% by mass or more and 50% by mass or less of a polyrotaxane (for example, see Japanese Patent Application Laid-Open No. 2019-125487). Summary of the Invention
[0006] However, in the stacked battery disclosed in Japanese Patent Application No. 2019-125487, although the corrosion caused by the short circuit between the aluminum layer and the negative electrode is suppressed by utilizing the high elasticity of the intermediate layer containing a specific amount of polyrotaxane, when the surface of the electrode collector is covered with an external film, contamination is buried in the electrode collector, and there is room for improvement in suppressing damage to the electrode collector.
[0007] The present invention provides a method for manufacturing an all-solid-state battery that prevents contamination present between the outer film and the electrode current collector from being buried in the electrode current collector and damaging the electrode current collector when the outer film is used to cover the surface of the electrode current collector. The present invention contributes to stabilizing battery performance and improving quality management during the manufacturing process.
[0008] The solution of the present invention provides the following method.
[0009] [1] A method for manufacturing an all-solid-state battery, wherein:
[0010] The manufacturing method of the all-solid-state battery has the following characteristics:
[0011] a heating step of heating at least a portion of the exterior film that faces the outermost surface of the electrode stack in the stacking direction; and
[0012] The step of housing the electrode stack is to house the outer film.
[0013] Before the exterior film contacts the electrode stack, at least the portion of the exterior film facing the outermost surface of the electrode stack in the stacking direction is preliminarily softened by heating. This allows the exterior film to easily absorb contamination even when contamination exists between the exterior film and the electrode current collector.
[0014] [2] The method for manufacturing an all-solid-state battery according to [1], wherein:
[0015] In the heating step, the temperature at which the portion is heated is a temperature exceeding the glass transition point of the resin constituting the portion.
[0016] By setting the temperature at which the above-mentioned portion is heated to a temperature exceeding the glass transition point of the resin constituting the above-mentioned portion, damage to the electrode stack due to heating of the exterior film can be suppressed.
[0017] [3] The method for manufacturing an all-solid-state battery according to [1] or [2], wherein:
[0018] The exterior film comprises a sealing resin layer, a metal layer and an outer resin layer.
[0019] The sealing resin layer, the metal layer, and the outer resin layer are stacked in this order.
[0020] As the exterior film, an exterior film having a sealing resin layer, a metal layer and an exterior resin layer is used. The sealing resin layer is pre-softened by heating, so that even if contamination exists between the exterior film and the electrode collector, the sealing resin layer can easily absorb the contamination.
[0021] [4] The method for manufacturing an all-solid-state battery according to [1] or [2], wherein:
[0022] The exterior film comprises a sealing resin layer, an insulating resin layer, a metal layer and an outer resin layer.
[0023] The sealing resin layer, the insulating resin layer, the metal layer, and the outer resin layer are stacked in this order.
[0024] The exterior film comprises a sealing resin layer, an insulating resin layer, a metal layer, and an exterior resin layer. When the electrode stack is housed within the exterior film, the insulating resin layer prevents short circuits between the metal layer and the electrode stack. Furthermore, the insulating resin layer within the exterior film provides durability against high loads during cycling.
[0025] [5] The method for manufacturing an all-solid-state battery according to [3] or [4], wherein:
[0026] The sealing resin constituting the sealing resin layer has a glass transition point of less than 45°C.
[0027] Since the glass transition point of the sealing resin constituting the sealing resin layer is lower than 45° C., the sealing resin layer is sufficiently softened in the heating step.
[0028] [6] The method for manufacturing an all-solid-state battery according to [4], wherein:
[0029] The insulating resin constituting the insulating resin layer has a glass transition point exceeding the glass transition point of the sealing resin constituting the sealing resin layer, and a melting point of 230° C. or higher.
[0030] By setting the glass transition point of the insulating resin constituting the insulating resin layer to a temperature higher than the glass transition point of the sealing resin constituting the sealing resin layer and having a melting point of 230°C or higher, it is possible to suppress softening of the insulating resin layer during the heating process and to suppress short circuiting between the metal layer and the electrode stack.
[0031] According to the aspects of the present invention, a method for manufacturing an all-solid-state battery can be provided that prevents contamination present between an exterior film and an electrode current collector from being buried in the electrode current collector and damaging the electrode current collector when the surface of the electrode current collector is covered with an exterior film. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a cross-sectional view showing an exterior film used in a method for manufacturing an all-solid-state battery according to one embodiment of the present invention.
[0033] Figure 2 This is a cross-sectional view showing an exterior film used in a method for manufacturing an all-solid-state battery according to one embodiment of the present invention. DETAILED DESCRIPTION
[0034] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the drawings used in the following description may be enlarged to facilitate understanding of features, and for convenience, the dimensional ratios of the various components are not limited to those shown.
[0035] [Manufacturing method of all-solid-state batteries]
[0036] The method for manufacturing an all-solid-state battery of this embodiment includes a heating step of heating at least a portion of an exterior film facing the outermost surface of an electrode stack in a stacking direction, and a housing step of housing the electrode stack in the exterior film.
[0037] "Electrode stack"
[0038] The electrode stack in this embodiment includes a positive electrode, a negative electrode, and an electrolyte layer.
[0039] (positive electrode)
[0040] The positive electrode is formed by laminating a first current collector layer and a first active material layer containing at least a positive electrode active material. In this embodiment, the positive electrode includes a first current collector layer and first active material layers formed on both main surfaces of the first current collector layer.
[0041] The first current collector layer is preferably composed of at least one substance having high electrical conductivity.
[0042] Examples of highly conductive materials include metals or alloys containing at least one of silver (Ag), palladium (Pd), gold (Au), platinum (Pt), aluminum (Al), chromium (Cr), and nickel (Ni), or non-metallic materials such as carbon (C). Considering both high conductivity and manufacturing cost, aluminum, nickel, or stainless steel are preferred. Furthermore, aluminum is less likely to react with the positive electrode active material and the electrolyte. Therefore, using aluminum in the first current collector layer can reduce the internal resistance of the battery.
[0043] The shape of the first current collector layer may be, for example, foil, plate, mesh, nonwoven fabric, foam, etc. In order to improve adhesion to the first active material layer, the surface of the first current collector layer may be provided with carbon or roughened.
[0044] The first active material layer contains a positive electrode active material that accepts electrons from lithium ions. The positive electrode active material is not particularly limited as long as it is a material that can reversibly release and absorb lithium ions and can transport electrons. A known positive electrode active material that can be applied to the positive electrode of a lithium ion battery can be used. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), solid solution oxide (Li2MnO3-LiMO2 (M=Co, Ni, etc.)), lithium-manganese-nickel-cobalt oxide (LiNi x Mn y Co zO2, x+y+z=1), composite oxides such as olivine-type lithium phosphorus oxide (LiFePO4); conductive polymers such as polyaniline and polypyrrole; sulfides such as Li2S, CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, and Li-Mo-S compounds; mixtures of sulfur and carbon; etc. The positive electrode active material can be composed of one of the above materials alone or of two or more.
[0045] The first active material layer includes an electrolyte that transfers lithium ions to and from the positive electrode active material. As an electrolyte, there is no particular limitation as long as it is an electrolyte with lithium ion conductivity, and materials commonly used in lithium ion batteries can be used. As electrolytes, for example, sulfide solid electrolyte materials, oxide solid electrolyte materials, halide solid electrolytes, inorganic solid electrolytes such as lithium salts, solid electrolytes of polymer systems such as polyethylene oxide, and gel-based solid electrolytes including ionic liquids containing lithium salts and lithium ion conductivity can be cited. Among them, from the perspective of higher lithium ion conductivity and pressure-based structural formability and good interface bonding, sulfide solid electrolyte materials are preferred.
[0046] The electrolyte may be composed of one of the above materials alone or of two or more. The electrolyte contained in the first active material layer may be the same material as or different from the electrolyte contained in the second active material layer and the solid electrolyte layer.
[0047] The first active material layer may also contain a conductive additive to improve the conductivity of the positive electrode. Any conductive additive commonly used in lithium-ion batteries can be used. Examples include carbon blacks such as acetylene black and Ketjen Black; carbon fibers; vapor-grown carbon fibers; graphite powder; and carbon nanotubes. The conductive additive may be composed of one of the above materials alone or a combination of two or more.
[0048] Furthermore, the first active material layer may contain a binder that has a function of binding the positive electrode active materials to each other and to the first current collector layer.
[0049] The first active material layer may be formed on both principal surfaces of the first current collector layer, or may be formed on only one principal surface of the first current collector layer. Furthermore, if the positive electrode is a single-sided coated electrode, a stacked positive electrode formed by stacking two positive electrodes with their current collector surfaces aligned may be used as a double-sided coated electrode. Furthermore, if the first current collector layer has a three-dimensional porous structure such as a mesh, non-woven fabric, or foam, the first current collector layer may be provided integrally with the first active material layer.
[0050] The first current collector layer is assembled at one end portion in the width direction of the all-solid-state battery.
[0051] The first active material layer is in contact with the electrolyte layer and therefore may contain sulfides contained in the electrolyte layer.
[0052] (negative electrode)
[0053] The negative electrode includes a second active material layer containing at least a negative electrode active material.
[0054] The second current collector layer contains, for example, copper (Cu). Like the first current collector layer, the second current collector layer may also contain substances other than copper with higher conductivity. Examples of substances other than copper with higher conductivity include metals or alloys containing at least one metal element of silver (Ag), palladium (Pd), gold (Au), platinum (Pt), chromium (Cr), and nickel (Ni), or non-metals such as carbon (C). When considering manufacturing costs in addition to high conductivity, nickel or stainless steel is preferred as a substance other than copper. In addition, stainless steel is difficult to react with the positive electrode active material, the negative electrode active material, and the electrolyte. Therefore, when stainless steel is used in the second current collector layer, the manufacturing cost of the battery can be reduced.
[0055] The second current collector layer may be shaped like a foil, a plate, a mesh, a nonwoven fabric, or a foam. In order to improve adhesion to the second active material layer, the surface of the second current collector layer may be provided with carbon or roughened.
[0056] The second active material layer contains a negative electrode active material that accepts electrons with lithium ions. As the negative electrode active material, there is no particular limitation as long as it is a material that can reversibly release and absorb lithium ions and can transport electrons. A known negative electrode active material that can be applied to the negative electrode of a lithium ion battery can be used. For example, carbonaceous materials such as natural graphite, artificial graphite, resin carbon, carbon fiber, activated carbon, hard carbon, and soft carbon; alloy materials based on tin, tin alloys, silicon, silicon alloys, gallium, gallium alloys, indium, indium alloys, aluminum, and aluminum alloys; conductive polymers such as polyacetylene, polyacetylene, and polypyrrole; metallic lithium; lithium-titanium composite oxides (such as Li4Ti5O 12 ) and other lithium alloys. These negative electrode active materials may be composed of one of the above materials alone or of two or more.
[0057] The second active material layer includes an electrolyte that transfers lithium ions to and from the negative electrode active material. As an electrolyte, there is no particular limitation as long as it is an electrolyte with lithium ion conductivity, and materials commonly used in lithium ion batteries can be used. As electrolytes, for example, sulfide solid electrolyte materials, oxide solid electrolyte materials, halide solid electrolytes, inorganic solid electrolytes containing lithium salts, solid electrolytes of polymer systems such as polyethylene oxide, and gel-based solid electrolytes including lithium salts and lithium ion conductive ionic liquids can be cited. The electrolyte can be composed of one of the above materials alone, or it can be composed of two or more.
[0058] The electrolyte contained in the second active material layer may be the same as or different from the electrolyte contained in the first active material layer and the solid electrolyte layer.
[0059] The second active material layer may also contain a conductive additive, a binder, etc. These materials are not particularly limited, but for example, the same materials as those used for the first active material layer described above can be used.
[0060] The second active material layer may be formed on both main surfaces of the second current collector layer, or may be formed on only one main surface of the second current collector layer. In addition, when the second current collector layer has a three-dimensional porous structure such as a mesh, non-woven fabric, or foam, the second current collector layer may be provided integrally with the second active material layer.
[0061] (Electrolyte layer)
[0062] The electrolyte layer is disposed between the first active material layer and the second active material layer.
[0063] As electrolyte, as long as it is an electrolyte with lithium ion conductivity and insulation, there is no particular limitation, and materials commonly used in lithium ion batteries can be used. For example, sulfide solid electrolyte materials, oxide solid electrolyte materials, halide solid electrolytes, inorganic solid electrolytes such as lithium salts, solid electrolytes of polymer systems such as polyethylene oxide, and gel electrolytes including ionic liquids containing lithium salts and lithium ion conductivity can be cited. Among them, from the viewpoint of the higher conductive properties of lithium ions and the structural formability and good interface bonding properties based on pressure, sulfide solid electrolyte materials are preferably used.
[0064] The form of the electrolyte material is not particularly limited, but an example thereof may be a particle form.
[0065] The electrolyte layer may contain a binder for imparting mechanical strength and flexibility.
[0066] The electrolyte layer may also be in the form of a sheet having a porous substrate and a solid electrolyte retained on the porous substrate. There is no particular limitation on the form of the porous substrate, but for example, woven fabrics, non-woven fabrics, meshes, porous membranes, expansion sheets, punching sheets, etc. may be cited. Among these forms, non-woven fabrics are preferred from the viewpoint of higher handling properties of the solid electrolyte filling amount.
[0067] The porous substrate is preferably made of an insulating material. This improves the insulation properties of the electrolyte layer. Examples of insulating materials include resin materials such as nylon, polyester, polyethylene, polypropylene, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polyvinylidene chloride, polyvinyl chloride, polyurethane, vinylon, polybenzimidazole, polyimide, polyphenylene sulfide, polyetheretherketone, cellulose, and acrylic resin; natural fibers such as hemp, wood pulp, and cotton linter; and glass.
[0068] Heating process
[0069] In the heating step, at least the portion of the outer film that covers and houses the electrode stack, facing the outermost surface of the electrode stack in the stacking direction, is heated. Even if contamination is present on the outermost surface of the electrode stack, the heating softens at least the portion of the outer film that faces the outermost surface of the electrode stack in the stacking direction. Therefore, when the outer film exerts a force that presses the contamination toward the outermost surface of the electrode current collector, the contamination is buried within the outer film, thereby preventing damage to the electrode current collector.
[0070] In the heating step, the temperature at which the above-mentioned portion is heated is preferably, for example, 45°C or higher and less than 80°C. When the temperature at which the above-mentioned portion is heated exceeds the glass transition point of the resin constituting the above-mentioned portion, the above-mentioned portion softens, and the outer film exerts a force that presses the contaminant toward the outermost surface of the electrode current collector, burying the contaminant in the outer film. The temperature at which the above-mentioned portion is heated can be 45°C or higher, or 60°C or higher.
[0071] When the exterior film according to the first embodiment or the second embodiment described later is used as the exterior film, the portion heated in the heating step is the sealing resin layer.
[0072] "Exterior film"
[0073] The exterior film used in the method for manufacturing the all-solid-state battery of this embodiment will be described.
[0074] (First embodiment)
[0075] Figure 1 This is a cross-sectional view showing a first embodiment of an exterior film used in the method for manufacturing an all-solid-state battery according to the present embodiment.
[0076] like Figure 1 As shown, the exterior film 1 includes a sealing resin layer 2, a metal layer 3, and an outer resin layer 4. The sealing resin layer 2, the metal layer 3, and the outer resin layer 4 are stacked in this order. The sealing resin layer 2 and the metal layer 3 are stacked via a first adhesive layer 5. The metal layer 3 and the outer resin layer 4 are stacked via a second adhesive layer 6. The sealing resin layer 2 is a portion facing the outermost surface of the electrode stack in the stacking direction. Therefore, in the method for manufacturing an all-solid-state battery of this embodiment, at least the sealing resin layer 2 is heated to soften it.
[0077] The sealing resin constituting the sealing resin layer 2 preferably has a glass transition point of, for example, less than 45°C. The melting point of the sealing resin constituting the sealing resin layer 2 is preferably, for example, 130°C or higher. By setting the glass transition point and melting point of the sealing resin within the above ranges and heating at a temperature exceeding the glass transition point and below the melting point, the sealing resin layer 2 can be sufficiently softened.
[0078] As the sealing resin, for example, one having a Rockwell hardness of less than 85 is preferable.
[0079] Examples of the sealing resin include modified polypropylene and polyethylene.
[0080] The thickness of the sealing resin layer 2 is preferably from 10 μm to 80 μm, more preferably from 10 μm to 40 μm. When the thickness of the sealing resin layer 2 is at least the lower limit, contaminants with a diameter (particle size) of 10 μm or greater can be absorbed within the sealing resin layer 2. When the thickness of the sealing resin layer 2 is at most the upper limit, the thickness of the sealing resin layer 2 can be suppressed.
[0081] Examples of the metal constituting the metal layer 3 include aluminum and the like.
[0082] The thickness of the metal layer 3 is preferably 20 μm or more and 120 μm or less, and more preferably 40 μm or more and 80 μm or less.
[0083] Examples of the resin constituting the outer resin layer 4 include polyesters such as polyethylene terephthalate.
[0084] Examples of the adhesive constituting the first adhesive layer 5 and the second adhesive layer 6 include epoxy resins and polyurethane resins.
[0085] The thickness of the first adhesive layer 5 and the second adhesive layer 6 is preferably 1 μm or more and 3 μm or less.
[0086] (Second embodiment)
[0087] Figure 2This is a cross-sectional view showing a second embodiment of the exterior film used in the method for manufacturing the all-solid-state battery of this embodiment.
[0088] like Figure 2 As shown, the exterior film 10 includes a sealing resin layer 11, an insulating resin layer 12, a metal layer 13, and an outer resin layer 14. The sealing resin layer 11, the insulating resin layer 12, the metal layer 13, and the outer resin layer 14 are stacked in sequence. The sealing resin layer 11 and the insulating resin layer 12 are stacked via a first adhesive layer 15. The insulating resin layer 12 and the metal layer 13 are stacked via a second adhesive layer 16. The metal layer 13 and the outer resin layer 14 are stacked via a third adhesive layer 17. The sealing resin layer 11 is a portion facing the outermost surface of the exterior film 10 in the stacking direction. Therefore, in the method for manufacturing an all-solid-state battery of this embodiment, at least the sealing resin layer 11 is heated to soften it.
[0089] The sealing resin constituting the sealing resin layer 11 is the same as the sealing resin constituting the above-mentioned sealing resin layer 2 .
[0090] The thickness of the sealing resin layer 11 is the same as the thickness of the sealing resin layer 2 described above.
[0091] The resin constituting insulating resin layer 12 preferably has a glass transition point exceeding the glass transition point of the sealing resin constituting the sealing resin layer, and a melting point of 230°C or higher. By setting the glass transition point and melting point of the resin constituting insulating resin layer 12 within the aforementioned ranges, softening of insulating resin layer 12 due to heating of the aforementioned portion can be suppressed.
[0092] Examples of the resin constituting the insulating resin layer 12 include polyethylene terephthalate, reinforced polypropylene containing fibers such as glass fibers, reinforced polyester containing fibers such as glass fibers, polyimide, and polybenzimidazole.
[0093] The thickness of the insulating resin layer 12 is appropriately adjusted according to the resin constituting the insulating resin layer 12 .
[0094] The metal constituting the metal layer 13 is the same as the metal constituting the above-mentioned metal layer 3 .
[0095] The thickness of the metal layer 13 is the same as the thickness of the metal layer 3 described above.
[0096] The resin constituting the outer resin layer 14 is the same as the resin constituting the outer resin layer 4 described above.
[0097] The thickness of the outer resin layer 14 is the same as the thickness of the outer resin layer 4 described above.
[0098] The adhesive constituting the first adhesive layer 15, the second adhesive layer 16, and the third adhesive layer 17 is the same as the adhesive constituting the first adhesive layer 5 and the second adhesive layer 6. The adhesive constituting the first adhesive layer 15, the adhesive constituting the second adhesive layer 16, and the adhesive constituting the third adhesive layer 17 may all be different, two of them may be the same, or all of them may be the same.
[0099] The thicknesses of the first adhesive layer 15 , the second adhesive layer 16 , and the third adhesive layer 17 are the same as the thicknesses of the first adhesive layer 5 and the second adhesive layer 6 .
[0100] Containment Process
[0101] In the housing step, the electrode stack is housed in the exterior film at least at a portion facing the outermost surface of the electrode stack in the stacking direction that has been heated in the heating step.
[0102] That is, in the housing step, the electrode stack is covered and surrounded by the exterior film so that at least the heated portion is in contact with the outermost surface of the electrode stack in the stacking direction.
[0103] Through the above steps, an all-solid-state battery including the electrode stack and the exterior film housing the electrode stack is obtained.
[0104] According to the method for manufacturing an all-solid-state battery of this embodiment, before the outer film contacts the electrode stack, at least the portion of the outer film facing the outermost surface of the electrode stack in the stacking direction is pre-softened by heating. This allows the outer film to easily absorb contamination even when contamination exists between the outer film and the electrode current collector.
[0105] Although the embodiments of the present invention have been described in detail above, the present invention is not limited to the above embodiments, and various modifications and changes can be made within the scope of the gist of the present invention described in the claims.
Claims
1. A method for manufacturing an all-solid-state battery, wherein: The manufacturing method of the all-solid-state battery has the following characteristics: a heating step of heating at least a portion of the exterior film that faces the outermost surface of the electrode stack in the stacking direction; and The step of housing the electrode stack is to house the outer film.
2. The method for manufacturing an all-solid-state battery according to claim 1, wherein: In the heating step, the temperature at which the portion is heated is a temperature exceeding the glass transition point of the resin constituting the portion.
3. The method for manufacturing an all-solid-state battery according to claim 1, wherein: The exterior film comprises a sealing resin layer, a metal layer and an outer resin layer. The sealing resin layer, the metal layer, and the outer resin layer are stacked in this order.
4. The method for manufacturing an all-solid-state battery according to claim 1, wherein: The exterior film comprises a sealing resin layer, an insulating resin layer, a metal layer and an outer resin layer. The sealing resin layer, the insulating resin layer, the metal layer, and the outer resin layer are stacked in this order.
5. The method for manufacturing an all-solid-state battery according to claim 3 or 4, wherein: The sealing resin constituting the sealing resin layer has a glass transition point of less than 45°C.
6. The method for manufacturing an all-solid-state battery according to claim 4, wherein: The insulating resin constituting the insulating resin layer has a glass transition point exceeding the glass transition point of the sealing resin constituting the sealing resin layer, and a melting point of 230° C. or higher.
Citation Information
Patent Citations
Laminate battery
JP2019125487A
Electrode manufacturing device for storage battery
JP2024058233A